2019
DOI: 10.1177/2333392819841223
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Health-Care Cost of Patients With Lung Cancer: A Retrospective Study

Abstract: Introduction: Lung cancer exerts a significant societal and health-care–related economic burden and chemotherapy drugs constitute a major factor of total direct cost. The aim of the present study was to assess the direct health-care cost of lung cancer in Greece by conducting a retrospective analysis on the last 6 months of life. Methods: The present study was based on both the medical data and costs of treatment of deceased adult patients who suffered from terminal sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…This is in line with the results of other studies published indicating that end of life is one of the most expensive periods of cancer treatment [28]. Calculations of an actual in-depth cost study on 230 patients with the majority of NSCLC (78%) in an advanced stage revealed that the key drivers of the last six month of life were CTx (39%), concomitant medication (14%) and cost of hospitalization (14%) [29]. Our cost-effectiveness analysis reveal, that the combinatorial therapy was not inferior against the treatment standard, as it resulted in relevant hospital savings for CTx plus add-on VA per gained survival year compared to CTx alone.…”
Section: Plos Onesupporting
confidence: 87%
See 1 more Smart Citation
“…This is in line with the results of other studies published indicating that end of life is one of the most expensive periods of cancer treatment [28]. Calculations of an actual in-depth cost study on 230 patients with the majority of NSCLC (78%) in an advanced stage revealed that the key drivers of the last six month of life were CTx (39%), concomitant medication (14%) and cost of hospitalization (14%) [29]. Our cost-effectiveness analysis reveal, that the combinatorial therapy was not inferior against the treatment standard, as it resulted in relevant hospital savings for CTx plus add-on VA per gained survival year compared to CTx alone.…”
Section: Plos Onesupporting
confidence: 87%
“…This is in line with the results of other studies published indicating that end of life is one of the most expensive periods of cancer treatment [ 28 ]. Calculations of an actual in-depth cost study on 230 patients with the majority of NSCLC (78%) in an advanced stage revealed that the key drivers of the last six month of life were CTx (39%), concomitant medication (14%) and cost of hospitalization (14%) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the results of other studies published indicating that end of life is one of the most expensive periods of cancer treatment [27]. Calculations of an actual in-depth cost study on 230 patients with the majority of NSCLC (78%) in an advanced stage revealed that the key drivers of the last six month of life were chemotherapy (39%), concomitant medication (14%) and cost of hospitalization (14%) [28]. To our knowledge, this is the first study to directly analyse the cost and cost effectiveness of chemotherapy plus VA therapy compared to chemotherapy alone in stage IV NSCLC patients based on real world patient data and hospital costs in Germany.…”
Section: Cost-effectivenesssupporting
confidence: 87%
“…Therefore, our findings may be a reflection of the profound impact that health policies and delivery at a state level have on clinical outcomes. Early detection and appropriate treatments for lung cancer, including surgical interventions and advanced therapies, lead to large health expenditures (30)(31)(32). For example, Vera-Llonch et al in their study, indicated that health care costs among patients with metastatic lung cancer receiving chemotherapy are substantial, exceeding $125,000 per patient over a mean follow-up period of 500 days.…”
Section: Discussionmentioning
confidence: 99%